A Comparative Investigation of the Analgesic Effects of Metamizole and Paracetamol in Rats. (1st June 2015) - Ince, Ilker; Aksoy, Mehmet; Ahiskalioglu, Ali; Comez, Mehmet; Dostbil, Aysenur; Celik, Mine; Yilmaz, Ismayil; Mammadov, Renad; Dogan, Hasan; Boztok Ozgermen, Basak; Altuner, Durdu
ABSTRACT Background: This study investigated the effects of metamizole and paracetamol on pain and oxidative stress induced by scalpel incision and carrageenan in rats. Materials and methods: Total of 144 rats were divided into groups of 12 animals. Six groups each were used for scalpel incision and carrageenan tests. Pain was inflicted by applying a scalpel incision or carrageenan. Pain-created groups by scalpel incision received metamizole (SIM) or paracetamol (SIP) at doses of 250 or 500 mg/kg. Pain-created groups by carrageenan received metamizole (CAM) or paracetamol (CAP) at doses of 250 or 500 mg/kg. Analgesic activity was determined by Basile Algesimeter. The COX-2 and MPO gene expressions were determined, and malondialdehyde and tGSH were measured in rat paws. Results: In the scalpel incision test, pain was reduced in groups of SIM-250 and SIM-500 in the first hour by 65.2% and 91.3%, respectively, and in the third hour by 51.9% and 77.8%, respectively, compared with the SIC group. In SIP-250 and SIP-500 groups, pain was reduced in the first hour by 43% and 74%, respectively, and by 33.4% and 59.3%, respectively, in the third hour compared with the SIC group. In the carrageenan test, in groups CAM-250 and CAM-500, pain was reduced in the first hour by 72.3% and 86.1%, respectively, and by 65.8% and 71.4%, respectively, in the third hour compared with the CCG group. In groups CAP-250 and CAP-500, pain was reduced in the first hour by 52.8% and 69.4%, respectively, and by 28.6% and 25.8%, respectively, in the third hour compared with the CCG group. Metamizole inhibited COX-2 gene expression at a dose of 500 mg/kg in the carrageenan test. At doses of 250 and 500 mg/kg, metamizole reduced COX-2 and MPO gene expressions and oxidative stress induced by scalpel incision or carrageenan. But both doses of paracetamol were unable to suppress that parameters. Conclusions: Our results show that metamizole is more effective than paracetamol for treating surgical trauma-related pain, inflammation, and oxidative stress and hence may be a preferential drug to paracetamol.